2023
DOI: 10.1021/acs.orglett.2c04314
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Cyclization of 2-Alkynylanilines to Give 2-Haloalkoxy-3-alkyl(aryl)quinolines

Abstract: Herein we describe a method to produce 2-haloalkoxy-3-substituted quinolines via the cyclization of 2-alkynylanilines with TMSCF3 and THF. This synthetic method uses inexpensive and easy-to-handle TMSCF3 and employs a commercially available CuI catalyst to transform a broad range of 2-alkynylanilines into versatile 2-difluoromethoxy-3-substituted quinolines and 2-iodoalkoxy-3-substituted quinolines with excellent chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Meanwhile, Qiu's group found that TMSCF 3 could be employed as a C1 source to undergo cyclization with 2-alkynylanilines and THF to produce 2-haloalkoxy-3-substituted quinolines with high chemoselectivity in the presence of a Cu (I) catalyst (Scheme 25b). 79 In 2023, Song and co-workers found that bromodifluoroacetate, as a useful precursor of difluorocarbene, underwent twofold C-F bond cleavage and insertion into the N-N bond of 2H-indazoles to assemble multifunctional quinazolin-4(3H)ones through a difluoro-ylide intermediate (Scheme 26). 80 The newly developed methods are further extended to modify bioactive molecules and natural products containing 2H-indazoles, which can deliver ring expansion products in moderate to good yields (76a-76e, 63%-88%).…”
Section: Cycloaddition and C-f Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Qiu's group found that TMSCF 3 could be employed as a C1 source to undergo cyclization with 2-alkynylanilines and THF to produce 2-haloalkoxy-3-substituted quinolines with high chemoselectivity in the presence of a Cu (I) catalyst (Scheme 25b). 79 In 2023, Song and co-workers found that bromodifluoroacetate, as a useful precursor of difluorocarbene, underwent twofold C-F bond cleavage and insertion into the N-N bond of 2H-indazoles to assemble multifunctional quinazolin-4(3H)ones through a difluoro-ylide intermediate (Scheme 26). 80 The newly developed methods are further extended to modify bioactive molecules and natural products containing 2H-indazoles, which can deliver ring expansion products in moderate to good yields (76a-76e, 63%-88%).…”
Section: Cycloaddition and C-f Functionalizationmentioning
confidence: 99%
“…Meanwhile, Qiu's group found that TMSCF 3 could be employed as a C 1 source to undergo cyclization with 2-alkynylanilines and THF to produce 2-haloalkoxy-3-substituted quinolines with high chemoselectivity in the presence of a Cu( i ) catalyst (Scheme 25b). 79…”
Section: Cycloaddition and C–f Functionalizationmentioning
confidence: 99%